# New monads

### From HaskellWiki

(Difference between revisions)

(Add MonadBase with liftBase to generalize liftIO) |
m (→MonadBase) |

## Revision as of 23:55, 11 August 2006

## Contents |

## MonadBase

It seems that the liftIO function from MonadIO can be generalized to access whatever the base of a transformer stack happens to be. So there is no need for a liftSTM, liftST, etc.

-- By Chris Kuklewicz module MonadBase(MonadBase,liftBase) where import Data.Monoid(Monoid) import Control.Monad.Trans(lift,MonadTrans) -- All the base monads with GHC import Control.Monad.ST.Strict as S(ST) import Control.Monad.ST.Lazy as L(ST) import Control.Concurrent.STM(STM) import Text.ParserCombinators.Parsec(GenParser) -- And all the MonadIO instances: import Control.Monad.List(ListT) import Control.Monad.Cont(ContT) import Control.Monad.Error(ErrorT,Error) import Control.Monad.Reader(ReaderT) import Control.Monad.State(StateT) import Control.Monad.Writer(WriterT) import Control.Monad.RWS(RWST) class (Monad m,Monad b) => MonadBase b m where liftBase :: b a -> m a -- Base monads instance MonadBase IO IO where liftBase = id instance MonadBase STM STM where liftBase = id instance MonadBase (GenParser tok st) (GenParser tok st) where liftBase = id instance MonadBase (S.ST s) (S.ST s) where liftBase = id instance MonadBase (L.ST s) (L.ST s) where liftBase = id instance MonadBase Maybe Maybe where liftBase = id instance MonadBase [] [] where liftBase = id instance (Error e) => MonadBase (Either e) (Either e) where liftBase = id instance MonadBase ((->) a) ((->) a) where liftBase = id -- Trans monads instance MonadBase b m => MonadBase b (ListT m) where liftBase = lift . liftBase instance MonadBase b m => MonadBase b (ContT r m) where liftBase = lift . liftBase instance (Error e, MonadBase b m) => MonadBase b (ErrorT e m) where liftBase = lift . liftBase instance MonadBase b m => MonadBase b (ReaderT r m) where liftBase = lift . liftBase instance MonadBase b m => MonadBase b (StateT s m) where liftBase = lift . liftBase instance (Monoid w, MonadBase b m) => MonadBase b (WriterT w m) where liftBase = lift . liftBase instance (Monoid w, MonadBase b m) => MonadBase b (RWST r w s m) where liftBase = lift . liftBase

And an artificial example:

module Main where import MonadBase import Control.Monad.Reader import Control.Monad.Writer type Foo a = (WriterT [Int] (ReaderT String [])) a foo :: Foo String foo = do x <- liftBase [1,2,3] s <- ask tell [succ x] return (s ++ show x) test = runReaderT (runWriterT foo) "hello"

*Main> test [("hello1",[2]),("hello2",[3]),("hello3",[4])]